Match or Mismatch: Strategy-Structure Configurations in the Service Business of Manufacturing Companies - Gebauer, Heiko; Edvardsson, Bo; Gustafsson, Anders; Witell, Lars (Journal of service research : JSR, 2010)
A new trend seems to be emerging for multinational manufacturing companies to make a strategic reorientation into becoming service providers. For some companies, such as Kone and IBM, the revenues from services are 50% or more of their total sales. Despite the increasing interest in exploring various aspects of the service part of the business in manufacturing companies, existing research has not focused on the interdependencies between different service strategies and organizational designs. This article studies different service strategies in manufacturing companies and highlights the organizational design necessary for implementing each service strategy. The service strategies explored are aftersales service providers, customer support service providers, outsourcing partners, and development partners. Each service strategy is supported by organizational design factors related to the service orientation of corporate culture, the service orientation of human resource management, and the service orientation of organizational structures. This research concludes that a specific strategy-structure configuration is needed in order to succeed with a chosen service strategy.